HbA1c levels and breast cancer prognosis in women without diabetes - Jonas Busk Holm; Jens Meldgaard Bruun; Peer Christiansen; Reimar Wernich Thomsen; Jan Frystyk; Deirdre Cronin-Fenton; Signe Borgquist (BMC Cancer)
Abstract Background Diabetes is associated with impaired breast cancer prognosis; however, the effectiveness of glycosylated hemoglobin (HbA1c) as a prognostic biomarker in breast cancer remains uncertain, especially for patients without diabetes. We aimed to determine whether elevated HbA1c is associated with a worse prognosis in breast cancer patients without known diabetes. Methods The study population comprised women with primary invasive stage I-III breast cancer between 2010 and 2020 surgically treated at Aarhus University Hospital, Denmark, without a diabetes diagnosis at baseline. We assessed HbA1c at breast cancer diagnosis as a categorical (quartiles; HbA1c-Q1 = 21–33 mmol/mol, HbA1c-Q2 = 34–36 mmol/mol, HbA1c-Q3 = 37–38 mmol/mol, HbA1c-Q4 = ≥ 39 mmol/mol) and log2-transformed continuous variable. Follow-up began at the date of primary breast cancer surgery and continued until the first occurrence of either a new breast cancer event (loco-regional or distant recurrence, or contralateral breast cancer), new primary cancer other than breast cancer, death, emigration, or end-of-follow-up (November 15th, 2021). Cox regression models estimated crude and adjusted hazard ratios and associated 95% confidence intervals (95% CIs) of a new breast cancer event and all-cause mortality, adjusting for patient characteristics based on a directed acyclic graph. The lowest HbA1c quartile (HbA1c-Q1) was used as reference. Results In total, 2514 women (median age 62 years) were included. During median 5.6 years follow-up for new breast cancer events, 230 (9.1%) events occurred. An escalating risk of new breast cancer events was observed with increasing HbA1c quartiles (adjusted hazard ratios, HbA1c-Q2: 1.09 [95% CI = 0.75–1.60]; HbA1c-Q3: 1.35 [95% CI = 0.88–2.07]; HbA1c-Q4: 1.69 [95% CI = 1.13–2.54]) compared to HbA1c-Q1. During median 6.0 years follow-up for all-cause mortality, 267 deaths (10.6%) occurred. No apparent association was evident between increasing HbA1c quartiles and all-cause mortality (adjusted hazard ratios, HbA1c-Q2: 0.75 [95% CI = 0.52–1.07]; HbA1c-Q3: 0.82 [95% CI = 0.55–1.21]; HbA1c-Q4: 1.06 [95% CI = 0.74–1.53]). Similarly, a log2(HbA1c) increase was associated with an increased risk of new breast cancer events, but not all-cause mortality. Conclusions For women with primary breast cancer and no known diagnosis of diabetes, higher levels of HbA1c were associated with an increased risk of new breast cancer events, but not all-cause mortality. HbA1c may serve as a prognostic metabolic biomarker for breast cancer patients without diabetes.